Herpes Zoster associated With COVID-19 in an immunocompetent male - Abdullah Al Faruk; Mohammad Rifat Rahman (Update Dental College, 2021)
Severe acute respiratory syndrome coronavirus (SARS-COV-2) presented with pulmonary symptoms and various extra pulmonary manifestations including dermatological manifestations like urticarial, acralvascular lesion erythematous maculopapular rash, and vesicular rash. Herpes zoster is a painful vesicular rash resulting from reactivation of varicella-zoster (VZ) virus that also a causative agent of chickenpox. The incidence of HZ infection (HZI) more prevalent in older ages and various immunosuppressive conditions. Coronavirus disease in 2019(Covid19) causing immune exhaustion and VZ virus reactivation, which is commonly presented as HZ in middle-aged adults. Here we report a case of HZ infection in association with COVID 19 positive 60 years male.  Update Dent. Coll. j: 2021; 11(2): 35-37